Building sustainable values in organizations with the support of human resource management: Evidence from one firm considered as the 'best place to work' in Brazil - De Souza Freitas, Wesley Ricardo; Jabbour, Charbel José Chiappetta [UNESP]; Mangili, Leandro Luis [UNESP]; Filho, Walter Leal; De Oliveira, Jorge Henrique Caldeira (My University, 2012)
Researchers and other professionals unanimously agree that companies should become more sustainable, but this will not happen without the support of human resource management. Paradoxically, there is a lack of information on the support human resource management offers to organizational sustainability applied to real cases. Therefore, this research presents a case study on this topic that was carried out in a leading Brazilian company, which is considered as a model and has been selected as 'the best place to work in the country'. The results provide practical examples of how this family company has been working to guarantee an increasingly sustainable performance with the support of human resources, highlighting the achievements and challenges the company has faced. One of the main results indicates that companies seeking to achieve sustainability need the assistance of the human resource field in order to design a communication system which bridges the gap between practices and sustainable values. © 2012 Management Centre for Human Values.
Keywords: Brazil; case study; Sustainability; sustainable human resource management; sustainable organizations